Debt financing and importance of fixed assets and goodwill assets as collateral: dynamic panel evidence - Matemilola, Bolaji Tunde; Ahmad, Rubi (VGTU Press, 2015)
This article analyses the effect of fixed assets and goodwill assets on South African firms’ debt ratios. The difference and system generalized method of moment estimation results reveal that fixed assets and goodwill assets have significant and positive relationship with firms’ debt ratios. To secure long-term debt, fixed assets and goodwill assets are required as collateral by creditors. Our results show firms’ adjust to long-run optimal debt level, but at a slow adjustment rate. Our results suggest there are costs preventing South African firms from adjusting faster to their long-run optimal debt level. The practical implication of the paper is that policy makers should promote policies that encourage further development of the capital market. Moreover, firms need both fixed assets and goodwill assets as collateral to raise the desired optimal debt that maximizes firm value.